Study on shear characteristics of calcareous sand with different particle size distribution - Zhang, Yongtao; Zhang, Ruiyuan; Yu, Chengcheng; Luo, Huiwu; Deng, Zhiqiang (Frontiers in Earth Science, 2023)
For the island and reef project formed by filling calcareous sand, the problem of the wide particle size distribution (PSD) and complex mechanical properties have to be faced. Therefore, in order to provide basic mechanical parameters for the construction of the island and reef project, the triaxial shear tests was carried out on calcareous sands with five different typical PSDs. The results showed that as the particle gradation became narrower, the axial strain corresponding to the strain softening point all showed a decreasing trend, and their differences gradually decreased, the confining pressure has a great impact on the volumetric deformation modulus of calcareous sand with a wide PSD. The cohesion of calcareous sand showed a positive correlation with the non-uniformity coefficient and curvature coefficient, while the variation of internal friction angle showed a parabolic law; the internal friction angle also changes in the parabola with the change of fine particle content. Furthermore, by establishing PFC3D discrete element model, it was found that the wider the particle gradation range, the greater axial strain corresponding to the critical coordination number; the sample with a narrow gradation interval was more likely to present a rotating displacement field to form a penetrating shear band.